Consumer skepticism toward cause-related marketing: An analysis on product quality and satisfaction of muslim consumers in Indonesia - Sakinah, Zahrah Riski; Gayatri, Gita (Islamic perspective on Communication and Psychology, 2024)
Background: This study aims to explore the influence of consumer skepticism on behavioral intentions among millennial Muslim consumers in Indonesia in the context of Cause-Related Marketing (CRM) programs. Skepticism towards corporate social initiatives may influence purchase decisions and consumer participation. Methods: This study uses a descriptive and cross-sectional approach by collecting data through a survey to 300 respondents who are millennial Muslim consumers. Data analysis was conducted using the regression analysis method to test the relationship between the variables of consumer skepticism and behavioral intention, as well as the moderating effect of religiosity. Findings: The results of the analysis show that 68% of respondents are skeptical of corporate social initiatives, and the resulting regression coefficient of -0.45 indicates that increased skepticism is negatively related to behavioral intention. In addition, situational factors such as corporate social motives and the image of non-profit organizations significantly contribute to the level of consumer skepticism. Product quality and satisfaction serve as mediators, while religiosity strengthens the impact of skepticism on behavioral intention. Conclusion: This research confirms that companies need to address consumer skepticism by increasing transparency and clarity of communication, and building a positive image through tangible commitments to social causes. Understanding religious values in marketing strategies can help increase positive behavioral intentions among millennial Muslim consumers. Novelty/Originality of this article: This article offers new insights into the relationship between consumer skepticism and behavioral intentions in the context of CRM, with a focus on millennial Muslim consumers in Indonesia, which has not been widely discussed in previous literature. This research also emphasizes the role of religiosity and product quality in shaping consumer attitudes and behaviors.